'Demand sharing' and more subtle language choice etiquettes for resource sharing in Northern Australia. Issue 3 (April 2019) - McConvell, Patrick
Abstract : Alfred Howitt, a leading nineteenth-century original anthropologist of Australian Aboriginal people, contributed a detailed account of the sharing of cuts of game according to kinship categories among the Kurnai of Victoria. Other accounts followed in the late twentieth century, some attending to the verbal negotiation involved. A characterisation of these events became dominant: demand sharing in which a person demands a share with a justification in terms of a kinship link. This paper shows that such negotiation over meat sharing among the Gurindji is more indirect, with choice of language varieties sending a pragmatic message that bonds between local groups of people imply responsibilities to give and rights to receive. In so doing, the paper defends the approach to code-switching that emphasises group identity and rights and responsibilities.